Lithium ion battery having positive electrode comprising NMC material as core and carbon black as shell
By using a positive active material with a core-shell particle structure of NMC material and carbon black in a lithium-ion battery, and optimizing the composition of the electrolyte solution and negative electrode, the shortcomings of existing lithium-ion batteries in terms of capacity, thermal stability and safety are solved and realized. Li-ion batteries with higher performance and longer life.
Patent Information
- Application Number
- CN202380047555.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-24
- Filing Date
- 2023-06-17
- Publication Date
- 2025-01-24
AI Technical Summary
Existing lithium-ion batteries still have shortcomings in improving capacity, thermal stability, weight and safety, especially in electric vehicles and electronic devices with high performance requirements.
The positive active material in the form of core shell particles, of which NMC materials are used as the core and carbon black as the shell, the weight ratio is 95.01: 4.99-99.5: 0.5, and optimize the electrolyte solution Formed additives, at the same time optimize the composition of negative electrodes.
It improves the capacity maintenance, thermal stability and safety of the lithium -ion battery, extend the service life of the battery, and optimize the overall performance of the battery.
Smart Images

Figure CN119365989A_ABST
Abstract
Description
Technical Field
[0001] Electrical and chemical engineering, relating to lithium-ion batteries having a positive electrode comprising NMC (nickel manganese cobalt) material as a core and carbon black as a shell. Background Art
[0002] A battery is an energy storage device that can convert chemical energy into electrical energy. Batteries can be divided into two categories, namely disposable primary batteries and rechargeable secondary batteries. The currently popular secondary battery is the lithium-ion battery, which uses lithium in the form of an inorganic compound that is able to generate electrical energy through the movement of lithium ions.
[0003] Lithium-ion batteries are very popular in the electronics and portable electrical devices and electric vehicle industries. Lithium-ion batteries can be produced in a variety of forms, such as button cells, cylindrical cells, pouch cells, and prismatic cells, depending on the application. In addition, there are battery packs for large-scale power generation, such as those in electric vehicles.
[0004] Lithium-ion batteries consist of a positive electrode, a negative electrode, an electrolyte solution, and a separator. The positive electrode contains a positive electrode active material that can absorb and release lithium ions, which is made of a lithium-containing material, such as lithium cobalt oxide (LiCoO2), which is the first positive electrode active material in the production of lithium-ion battery positive electrodes, but has low safety; lithium manganese oxide (LiMn2O4), which has high thermal stability and safety, but low cycle life; lithium iron phosphate (LiFePO4), which has high safety, small size, high stability, and long service life, but has lower energy density than other types of lithium batteries. In addition, there is lithium nickel manganese cobalt oxide (NMC material, or LiNMC or NMC), which contains nickel, manganese, and cobalt in different element ratios. For example, NMC111 is a LiNMC containing 1:1:1 nickel: manganese: cobalt, or NMC811 contains 8:1:1 nickel: manganese: cobalt. LiNMC takes advantage of the good properties of nickel, manganese, and cobalt. For example, nickel has high specific energy, but low stability, while manganese has low internal resistance. The combination of these elements gives lithium materials strength and thermal stability, making them suitable for uses such as in electric vehicles, which require high battery capacity and low heat generation.
[0005] However, in order to improve the conductivity of the positive electrode, the positive electrode active material has been made of NMC material, whose structure contains a metal oxide as a core, and a shell (core-shell particles, core@shell), wherein the shell helps to increase the energy from the electrolyte adsorption surface and improve the conductivity, which may affect the performance and service life of the battery. These inventions have been disclosed in various patents. For example:
[0006] The Chinese patent application with publication number CN108539193A invented a positive electrode, the positive electrode active material includes NMC material as a core and carbon nanotubes as a shell, the ratio of the carbon nanotube shell is 0.01-5wt% of the NMC material core, wherein the particle size of the NMC material core is 5-15 microns. The invented positive electrode has a charge of 2.5-4.5V, an initial charge / discharge rate of more than 240mAh / g (milliampere hours per gram), and a capacity retention rate of 90% at 100 charging cycles.
[0007] The Chinese patent application with publication number CN111354936A produces a positive electrode comprising an NMC material as a core and a carbon shell containing nano magnesium oxide or aluminum oxide.
[0008] The Chinese patent application with publication number CN112331830A proposes an invention of a positive electrode of a lithium-ion battery comprising an NMC material as a core and an outer shell. The NMC material core can be selected from NMC111, NMC532 or NMC811, and graphene is used as an outer shell, wherein the ratio of the NMC material core to the graphene outer shell is 1:0.005-0.1, and the ratio of the NMC material core and the graphene outer shell to the acetylene black type conductive material and the polyvinylidene fluoride (PVDF) type binder used is 80:10:10.
[0009] Based on the above information about lithium-ion batteries, we find that the positive electrode has a variety of compositions and is an important variable that affects the performance and characteristics of the battery. The negative electrode, electrolyte solution, and separator are also critical. The negative electrode contains a negative electrode active material, which is carbon (such as graphite or nanocarbon) or a lithium-containing material. The production of the negative electrode can combine the negative electrode active material with a conductive material and a binder to improve the performance of the negative electrode.
[0010] The electrolyte solution contains lithium salts, and commonly used ones are lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), etc. These lithium salts are dissolved in organic solvents, such as ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate (PC), etc. In addition, there is a separator, which keeps the positive and negative electrodes separated to avoid contact, generally a polymer, such as polyethylene (PE), polypropylene (PP), etc. Inventions related to lithium-ion batteries using positive electrodes, negative electrodes and electrolyte solutions have been disclosed in various patents. For example:
[0011] The U.S. patent application with publication number US20210159541A1 invented a battery having a positive electrode and a negative electrode, wherein the positive electrode uses a positive electrode active material (NMC111 material) combined with conductive carbon and polyvinylidene fluoride (PVDF) type binder, and the negative electrode uses a negative electrode active material (artificial graphite) combined with styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC). An electrolyte solution is used, in which the lithium salt is lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium tetrafluoroborate (LiBF4), and the molar ratio thereof is 1: 0.01-1.2: 0.05-0.7. In addition, a solvent mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) can also be used. Vinylene carbonate (VC), fluoroethylene carbonate (FEC) and propane sultone (PS) account for 1-10wt% of the electrolyte solution as additives.
[0012] The negative electrode active material used in the European patent application with publication number EP39168504A4 is artificial graphite, and the negative electrode retaining material used in the US patent with patent number US11152621B2 is artificial graphite, but the surface is modified by adding nitrogen atoms. The US patent with patent number US10897062B2 produces a battery whose positive electrode contains NMC material; the negative electrode contains graphite coated with amorphous carbon; lithium bis (fluorosulfonyl) imide (LiFSI) and lithium hexafluorophosphate (LiPF6) electrolyte solution in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC); and lithium difluorophosphate (LiPO2F2) additive.
[0013] In addition, there is a research journal with related inventions, namely the Energy Storage Materials journal, which published a study entitled "Core-shell Ni-rich NMC-nanocarbon positive electrode from scalable solvent-free mechanofusion for high-performance 18650 Li-ion batteries", which produced positive electrode active materials in the form of a structure containing NMC material as a core (using NMC811 material) and a nanocarbon shell, and the weight ratio of NMC material to nanocarbon is 90%:10%. The nanocarbon used is a carbon black type, and a structure containing NMC material as a core and nanocarbon as a shell is formed by mechanical melting. In addition, carbon black is used as a conductive material and polyvinylidene fluoride (PVDF) is used as a binder to make the positive electrode of the battery. The battery is made into a 18650 cylindrical battery using a weight ratio of 946:24:3 corresponding to the NMC material as a core and nanocarbon as a shell and carbon black and polyvinylidene fluoride (PVDF) as a conductive material. The electrolyte solution used contains 10 moles of lithium hexafluorophosphate (LiPF6) in a solvent, wherein the solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1. The negative electrode used is composed of a graphite-type negative electrode active material, carbon black as a conductive material, and polyvinylidene fluoride (PVDF) as a binder, with a corresponding weight ratio of 96.6:1.7:1.7. In addition, a button battery was invented, using lithium as the negative electrode, and the positive electrode contained an NMC material as a core and nanocarbon as a shell, and carbon black and polyvinylidene fluoride as a conductive material in a corresponding weight ratio of 80:10:10.
[0014] In addition to the foreign patents mentioned above, there are also some patents applied for in Thailand that disclose inventions related to lithium-ion batteries. For example:
[0015] The Thai patent application with publication number 1601000751 invented a positive electrode of a lithium-sulfur battery in the form of a core and shell structure, using sulfur as the core and nanocarbon as the shell, the weight ratio of the two is 95:5 respectively, and mechanical melting is used to form the material into a core and shell structure, wherein the corresponding weight ratio of the sulfide-containing positive electrode with nanocarbon as the shell to the nanocarbon-type conductive material and the polyvinylidene fluoride (PVDF)-type binder is 6:3:1.
[0016] The Thai patent application with publication number 1601000853 invented an electrode composed of NMC material as a positive electrode active material, and the corresponding weight ratio of the positive electrode active material to the nanocarbon type conductor and the polyvinylidene fluoride (PVDF) type binder is 8:1:1. The Thai patent application with publication number TH1601001280 invented a positive electrode of a lithium-ion battery in the form of a core and shell structure, using lithium polysulfide as the core and nanocarbon as the shell, the weight ratio of the two is 95:5, and the corresponding weight ratio of the positive electrode composed of lithium sulfide with a nanocarbon shell to the nanocarbon type conductive material and the polyvinylidene fluoride (PVDF) type binder is 6:3:1.
[0017] The Thai patent application with publication number 1801007531 invents a positive electrode of a lithium-ion battery, wherein the positive electrode active material comprises lithium nickel aluminum oxide as a core and nanocarbon as an outer shell, and the weight ratio thereof is 70-95:5-30.
[0018] Thailand patent application with publication number 1801005876 proposes a process for manufacturing lithium-ion battery electrodes, wherein the positive electrode comprises lithium metal silicate, which is mixed with a carbon-type conductor and a binder such as polyvinylidene fluoride (PVDF). The resulting mixture is coated on aluminum foil, and the resulting lithium-ion battery has an initial discharge of 1950 mAh / g at a battery discharge rate (C-rate) of 0.05.
[0019] The Thai patent application with publication number 1501005436 invented a negative electrode, which uses silicon as the negative electrode active material, graphene as a conductor, and polyacrylic acid as a binder, and the weight ratio of the three is 15-85:3-75:3-60 respectively.
[0020] Although many lithium-ion batteries and their components have been invented, the industry still needs to develop lithium-ion batteries with higher performance (improved capacity, thermal stability, weight and safety). Therefore, in order to improve the performance of lithium-ion batteries, the present invention has developed a positive electrode whose positive electrode active material comprises an NMC material core and a carbon black shell, improved electrolyte solution to improve performance, used additives that help minimize adverse reactions (which may generate gas in the system and affect service life), and also optimized the negative electrode composition of the battery. Summary of the invention
[0021] In order to produce a high-performance lithium-ion battery, the focus is on improving the positive electrode, and the positive electrode active material in the form of core-shell particles is used. The core uses NMC material (LiNMC or NMC), and carbon black is used as the shell, wherein the weight ratio of the NMC material used as the core of the positive electrode to the carbon black used as the shell ranges from 95.01:4.99 to 99.5:0.5. In addition, an electrolyte solution is provided so that it has the characteristic of minimizing pores using additives.
[0022] The present invention relates to a method for preparing a lithium ion battery, wherein the method comprises the following steps:
[0023] A. Mix materials for making positive electrodes, including positive electrode active materials, conductors and binders, wherein the positive electrode active materials are in the form of core-shell particles, the core used is NMC material, and carbon black is used as the shell. The prepared positive electrode is coated on aluminum foil.
[0024] B. Mixing materials for making a negative electrode, including a negative electrode active material, a possible conductor and a binder; and coating the prepared negative electrode on a copper foil according to the type of the negative electrode.
[0025] C. preparing an electrolyte solution, the electrolyte solution comprising a lithium salt, a solvent and an additive.
[0026] D. Assembling a lithium-ion battery using the positive electrode prepared in step A, the negative electrode prepared in step B, a polymer film as a separator, and the electrolyte solution as an ion conductor prepared in step C. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 .Capacity of button cells at different battery charge / discharge rates (C-rates).
[0028] Figure 2 Capacity retention (percent) of pouch cells using 2% vinylene carbonate (VC) and 0-10% fluoroethylene carbonate (FEC) additives based on electrolyte solution weight.
[0029] Figure 3 Capacity retention (percent) of pouch cells using 2% vinylene carbonate (VC) and 0.1% fluoroethylene carbonate (FEC) additives by weight of electrolyte solution at battery charge / discharge rates (C-rates) of 0.5C and 1.0C. DETAILED DESCRIPTION
[0030] The present invention discloses below a lithium ion battery having a positive electrode including an NMC material as a core and carbon black as an outer shell and a process for manufacturing the battery.
[0031] The positive electrode contains a positive electrode active material that can absorb and release lithium ions, and is made of a lithium-containing material in the form of core-shell particles (core@shell), wherein the metal oxide core is lithium nickel manganese cobalt oxide (NMC material or LiNMC or NMC), the shell is carbon black, and the weight ratio of the NMC material as the core to the carbon black as the shell is 95.01:4.99-99.5:0.5. The preferred weight ratio range is 98:2-99:1. The most preferred weight ratio is 99:1. In addition, the positive electrode also includes carbon as a conductive material and a binder for the positive electrode, wherein the composition ratio of the NMC material core and the carbon black shell (NMC@C) to the carbon used as a conductive material and the binder is 80-99:0.5-10:0.5-10 (by weight). The optimal composition ratio of the NMC material core and the carbon black shell (NMC@C) to the carbon used as a conductive material and the binder is 94:4:2 (by weight).
[0032] The carbon used as the conductive material can be selected from any one or a combination of carbon black, nanocarbon, graphite, wherein the best carbon used as the conductive material is carbon black. The binder used for the positive electrode can be selected from any one or a combination of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose, butadiene rubber, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA) or polyacrylic acid, wherein the most preferred binder for the positive electrode is polyvinylidene fluoride (PVDF).
[0033] According to the form of the invented lithium ion battery, the negative electrode comprises any one or a combination of graphite carbon, oxide material or lithium to form a negative electrode active material, wherein the negative electrode prepared by graphite carbon and / or oxide material includes carbon as a conductive material and a binder for the negative electrode. The most preferred graphite carbon is artificial graphite. The carbon used as a conductive material can be selected from any one or a combination of carbon black, nanocarbon, and graphite, wherein the best carbon used as a conductive material is carbon black. The binder for the negative electrode can be selected from any one or a combination of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose, butadiene rubber, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA) or polyacrylic acid, wherein the most preferred binder for the negative electrode is carboxymethyl cellulose (CMC) and / or styrene-butadiene rubber (SBR).
[0034] The negative electrode has a negative electrode active material having a composition ratio of: graphite type carbon or oxide material: carbon used as a conductive material: carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) of 80-98.5:0.5-10:0.5-5:0.5-5 (by weight). The optimal composition ratio is 94.5:1:2.25:2.25 (by weight). The most preferred negative electrode active material is artificial graphite, which is used to prepare the negative electrode according to the above composition.
[0035] The electrolyte solution comprises a lithium salt and a solvent, wherein:
[0036] A. The lithium salt is lithium hexafluorophosphate (LiPF6) with a concentration range of 1.0-1.5 molar; the most preferred concentration is 1.2 molar.
[0037] B. The solvent can be selected from any one of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) or a combination thereof, wherein the solvent ratio comprises: ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) is 5-30:5-40:30-90 (by weight), and the optimal solvent ratio is 25:5:70 (by weight).
[0038] C. The additive may be selected from any one or a combination of vinylene carbonate (VC), fluoroethylene carbonate (FEC), propane sultone (PS), lithium difluorophosphate (LiPO2F2), and methylene disulfonate (MMDS), and the amount of the additive is 0.1-12% by weight of the electrolyte solution, wherein the preferred additive includes 2% by weight of the electrolyte solution of vinylene carbonate (VC) and 0.1-10% by weight of the electrolyte solution of fluoroethylene carbonate (FEC), propane sultone (PS), lithium difluorophosphate (LiPO2F2) or methylene disulfonate (MMDS) additives or any one or a combination thereof. The most preferred additive amount includes 2% of vinylene carbonate (VC) and 0.1% of fluoroethylene carbonate (FEC) (by weight of the electrolyte solution).
[0039] As described above, the most preferred electrolyte solution includes 1.2 moles of lithium hexafluorophosphate, wherein the weight ratio of solvent ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) is 25:5:70 respectively, and the corresponding amounts of vinylene carbonate (VC) and fluoroethylene carbonate (FEC) additives are 2% and 0.1% by weight of the electrolyte solution.
[0040] The preparation of a lithium-ion battery having a positive electrode including an NMC material as a core and carbon black as an outer shell includes the following steps.
[0041] A. Prepare a positive electrode, use mechanical melting to mix lithium manganese cobalt oxide (NMC) as a core with carbon black as a shell to prepare a positive electrode active material, wherein this method causes small particles to be compressed and adhere to each other due to the introduced energy; then mix the positive electrode active material with carbon used as a conductive material and a binder; then coat the prepared positive electrode on an aluminum foil; and then dry.
[0042] B. Preparation of negative electrode can be divided into two processes according to the negative electrode active material, among which:
[0043] The first process, when using graphite-type carbon and / or oxide materials as negative electrode active materials, includes the step of grinding the graphite-type carbon or oxide materials using a high-energy ball mill. Then, carbon, a binder and an organic solvent used as a conductive material are added, wherein the organic solvent can be selected from any one of N-methyl-2-pyrrolidone, ethanol or water or a combination thereof; then the prepared negative electrode is coated on a copper foil; and then dried.
[0044] The second process uses a negative electrode comprising a negative electrode active material, wherein the negative electrode active material is lithium metal in the form of a lithium metal sheet.
[0045] C. Prepare an electrolyte solution containing lithium hexafluorophosphate (LiPF6) salt, solvent and additives.
[0046] D. Assemble a lithium-ion battery using the positive electrode prepared in step A, the negative electrode prepared in step B, a polymer film as a separator, and the electrolyte solution prepared in step C as ion transport.
[0047] According to A and B, the weight range of the positive electrode prepared and coated on the aluminum foil is 17-23 mg per square centimeter and the thickness range is 110-250 μm. When using the negative electrode active material of graphite type carbon or oxide material, the weight range of the negative electrode prepared and coated on the copper foil is 10-15 mg per square centimeter and the thickness range is 100-250 μm.
[0048] According to A, in the step of making a positive electrode active material, the positive electrode contains a positive electrode active material in the form of core-shell particles (core@shell), the core-shell particles are NMC materials (LiNMC or NMC) as metal oxide cores, and carbon black as shells (NMC@C), wherein the ratio of the NMC material as the core to the carbon black as the shell contained in the material is in the range of 95.01:4.99-99.5:0.5 (by weight), and the preferred ratio range is 98:2-99:1 (by weight). The most preferred ratio is 99:1 (by weight). In addition, the positive electrode has a NMC material core and a carbon black shell: the carbon used as a conductive material: the binder has a ratio of 80-99:0.5-10:0.5-10 (by weight). The best positive electrode ratio is 94:4:2 (by weight). The carbon used as a conductive material can be selected from any one or a combination of carbon black, nanocarbon or graphite, wherein the best carbon used as a conductive material is carbon black. The binder for the positive electrode can be selected from any one of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose, butadiene rubber, styrene-butadiene rubber, polyvinyl alcohol (PVA) or polyacrylic acid, or a combination thereof, wherein the most preferred binder for the positive electrode is polyvinylidene fluoride (PVDF).
[0049] According to B, the negative electrode preparation step of the first process using a negative electrode active material of graphite-type carbon and / or oxide material includes carbon used as a conductive material and a binder for the negative electrode. The most preferred negative electrode active material of graphite-type carbon is artificial graphite; the carbon used as a conductive material can be selected from any one of carbon black, nanocarbon, and graphite or a combination thereof, wherein the best carbon used as a conductive material is carbon black; the binder used for the negative electrode can be selected from any one of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose, butadiene rubber, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA) or polyacrylic acid or a combination thereof, wherein the most preferred binder for the negative electrode is carboxymethyl cellulose (CMC) and / or styrene-butadiene rubber (SBR). The negative electrode has a preferred composition ratio including: negative electrode active material of graphite type carbon or oxide material: carbon used as conductive material: carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) corresponding to 80-98.5:0.5-10:0.5-5:0.5-5 (by weight). The best negative electrode composition ratio is 94.5:1:2.25:2.25 (by weight). The most preferred negative electrode active material is artificial graphite, which is used to prepare the negative electrode according to the composition.
[0050] According to C, the prepared electrolyte solution includes: 1.0-1.5 moles of lithium hexafluorophosphate (LiPF6); a solvent, which can be selected from any one or a combination of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC); an additive, which can be selected from any one or a combination of vinylene carbonate (VC), fluoroethylene carbonate (FEC), propane sultone (PS), lithium difluorophosphate (LiPO2F2) and methylene disulfonate (MMDS), and the total amount is 0.1-12% of the weight of the electrolyte solution. The most preferred concentration of lithium hexafluorophosphate (LiPF6) in the solvent mixture is 1.2 moles, wherein the weight ratio of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in the solvent mixture is 5-30:5-40:30-90, wherein the best solvent weight ratio is 25:5:70. The amount of vinylene carbonate (VC) additive is 2% by weight of the electrolyte solution, combined with the other additives mentioned above in an amount of 0.1-10% by weight of the electrolyte solution, wherein the most preferred additive consists of vinylene carbonate (VC) in an amount of 2% by weight of the electrolyte solution and fluoroethylene carbonate (FEC) in an amount of 0.1% by weight of the electrolyte solution.
[0051] The following are examples of preparation of a lithium ion battery having a positive electrode including an NMC material as a core and carbon black as an outer shell, and performance tests of the prepared battery with reference samples, but the present invention is not limited to these examples.
[0052] Example A: The invention of the lithium-ion button battery
[0053] Lithium-ion button cells were prepared with a positive electrode comprising a positive electrode active material (LiNMC@C or NMC@C) in the form of an NMC material as a core and carbon black as an outer shell, and the production steps were as follows:
[0054] 1. Prepare the positive electrode of the lithium-ion button battery. The material containing the NMC material is mixed for 1 to 10 minutes by mechanical melting, and then carbon black is added and stirred for 1 to 60 minutes. The weight ratio of the NMC material to the carbon black is 98:2 and 99:1 respectively, and a positive electrode active material having an NMC material core and a carbon black shell is obtained. The obtained positive electrode active material is mixed with carbon black as conductive carbon and a polyvinylidene fluoride (PVDF) binder in a ratio of 94:4:2 (in parts by weight). The NMC material used is NMC622, to which an organic solvent, namely N-methyl-2-pyrrolidone solution, is added.
[0055] 2. An electrolyte solution is prepared using 1.2 mol of lithium hexafluorophosphate (LiPF6) in a solvent mixture, wherein the ratio of ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) in the solvent mixture is 25:5:70 (by weight of the electrolyte solution), and two additives, namely vinylene carbonate (VC) and fluoroethylene carbonate (FEC), are used in amounts of 2% and 0.5% respectively (by weight of the electrolyte solution).
[0056] 3. Assemble a lithium-ion button cell using the prepared positive electrode and electrolyte solution. The negative electrode uses lithium and a polymer film separator made of polyethylene. A CR2032 button cell was produced.
[0057] The prepared lithium-ion button cell was tested for capacity, and the battery charge / discharge rate (C-rate) was controlled at 0.1C to 5.0C at 3.0 to 4.2V and 25 degrees Celsius for 5 cycles. Figure 1 , the battery capacity of the positive electrode active material being the NMC material without the shell decreased more than the battery capacity of the electrode active material being the NMC material core and the carbon black shell. In addition, it was also found that at a C-rate of 0.1C, the material having 1% of the carbon black used as the shell or the weight ratio of the NMC material to the carbon black being 99:1 had a higher capacity retention than the material having 2% of the carbon black used as the shell or the weight ratio of the NMC material to the carbon black being 98:2.
[0058] In the case where the C-rate is 3C or above, when the amount of carbon black used as the shell is increased to 2% or the weight ratio of the NMC material to the carbon black is 98:2, it is found that the decrease in the charge capacity is less than when the amount of carbon black used as the shell is 1% or the weight ratio of the NMC material to the carbon black is 99:1.
[0059] Therefore, the test in this embodiment shows that the use of NMC material core and carbon black shell as positive electrode active material of lithium ion battery helps to improve battery performance, especially when the weight ratio of NMC material to carbon black shell is 99:1 when the battery charge / discharge rate is 0.1-2.0C.
[0060] Example B: Invention of Lithium-ion Pouch Cells
[0061] 1. Prepare a positive electrode for a lithium-ion pouch cell using the same ingredients and process as in step 1 of example A, wherein for a positive electrode active material having an NMC material core and a carbon black shell, the weight ratio of the NMC material to the carbon black is selected to be 99:1; coat on aluminum foil; and then dry.
[0062] 2. Prepare the negative electrode of the lithium-ion pouch battery, using artificial graphite as the negative electrode active material, grinding the artificial graphite by using a high-energy ball mill; then mix it with carbon black as conductive carbon and two binders, namely styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC). The prepared negative electrode has artificial graphite: carbon black as conductive carbon: styrene-butadiene rubber (SBR): carboxymethyl cellulose (CMC) in a ratio of 94.5:1:2.25:2.25. In addition, an organic solvent selected from ethanol and / or water is added, wherein the mixed volume ratio of ethanol and water used in Example B is 30:70. It is coated on a copper foil and then dried.
[0063] 3. Prepare an electrolyte solution, using 1.2 moles of lithium hexafluorophosphate (LiPF6) in a solvent mixture, wherein the ratio of ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) in the solvent mixture is 25:5:70 by weight of the electrolyte solution; use a combination of two additives, the first additive is vinylene carbonate (VC), and the amount is 2% by weight of the electrolyte solution; the second additive can be selected from any one or a combination of fluoroethylene carbonate (FEC), propane sultone (PS) and lithium difluorophosphate (LiPO2F2), methylene methanedisulfonate (MMDS), and the amount is 0.1-10% by weight of the electrolyte solution.
[0064] 4. Assemble a lithium-ion pouch battery using the prepared positive electrode (in an amount of 17-23 mg per square centimeter), the prepared negative electrode (in an amount of 10-15 mg per square centimeter), the prepared electrolyte solution (in an amount of 18-20% of the battery weight) and a polymer film separator made of polyethylene, wherein the capacity of the prepared lithium-ion pouch battery is 200 milliampere hours (mAh).
[0065] Lithium ion pouch cells prepared using a combination of two additives (wherein the first additive was vinylene carbonate (VC); the second additive used helped to minimize gas formation in the electrolyte solution during charge / discharge and helped to minimize potential reactions in the system) were tested and studied at 2.7-4.2 volts and 25 degrees Celsius; the charge / discharge rate (C-rate) of the cell was controlled at 1.0C as shown in Table 1, and when the second additive (at an amount of 1% by weight of the electrolyte solution) and the first additive (at an amount of 2% by weight of the electrolyte solution) were used, it was found that the second additive used was propane sultone (PS) and the first additive was vinylene carbonate (VC) was most helpful in reducing the gas formed. In addition, when comparing the amount of the second additive (fluoroethylene carbonate (FEC), used at an amount of 0.1%, 1.0% and 10% by weight of the electrolyte solution), it was found that as shown in Table 1, the higher the amount of fluoroethylene carbonate (FEC), the less gas formed in the electrolyte solution.
[0066] Table 1. Type and amount of the second additive used in a 1.2 molar lithium hexafluorophosphate (LiPF6) electrolyte solution in a solvent mixture, wherein the weight ratio of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate (EC:EMC:DMC) in the solvent mixture is 25:5:70 respectively, and the first additive is vinylene carbonate (VC), accounting for 2% of the weight of the electrolyte solution.
[0067]
[0068]
[0069] However, when the second additive used was fluoroethylene carbonate (FEC) at 0.1%, 1.0% and 10% by weight of the electrolyte solution, and the first additive was vinylene carbonate (VC) at 2% by weight of the electrolyte solution, the battery charge / discharge rate (C-rate) was controlled at 0.5C, as shown in FIG. Figure 2 As shown, when testing the battery capacity performance, it was found that when the number of cycles was high, the battery capacity dropped rapidly when the amount of fluoroethylene carbonate (FEC) added was 1.0% and 10% by weight of the electrolyte solution, compared to not using fluoroethylene carbonate (FEC). However, compared to using 1.0% and 10% fluoroethylene carbonate (FEC) by weight of the electrolyte solution, it was found that the battery capacity drop was minimal when using 0.1% fluoroethylene carbonate (FEC) by weight of the electrolyte solution, and it was better than using vinylene carbonate (VC) alone. In addition, Figure 3The battery was tested at charge / discharge rates (C-rates) of 0.5C and 1.0C, using additives of 2% vinylene carbonate (VC) and 0.1% fluoroethylene carbonate (FEC) (by weight of the electrolyte solution). The study found that after 400 charge / discharge cycles, the battery capacity was still greater than 90% of the original capacity.
[0070] According to the above tests, it is found that each additive not only helps to minimize the formation of gas in the electrolyte solution, but also affects other performance aspects of the battery, such as charging / discharging, conductivity, stability in use, etc. Therefore, the optimized type and amount of additives can lead to optimized battery performance. It has been found that a lithium ion pouch battery using the above-provided positive and negative electrode components and an electrolyte solution in which the additives are vinyl carbonate (VC) and fluoroethylene carbonate (FEC) (2% and 0.1% by weight of the electrolyte solution, respectively) will be the best performing lithium ion battery.
[0071] Best Mode of Invention
[0072] As described in the specific implementation manner.
Claims
1. A lithium ion battery, the positive electrode of which comprises an NMC material as a core and carbon black as a shell, wherein the lithium ion battery comprises a positive electrode, a negative electrode, a polymer film as an electrode separator, and an electrolyte solution; The positive electrode comprises a positive electrode active material in the form of a metal oxide core and a shell (core@shell); that is, NMC material (LiNMC or NMC) as the metal oxide core and carbon black as the shell (NMC@C), wherein the weight ratio of the NMC material (LiNMC or NMC) as the core to the carbon black as the shell is in the range of 95.01:4.99-99.5:0.5; The positive electrode further includes carbon as a conductive material and a binder.
2. A lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 1, wherein the negative electrode comprises a negative electrode active material, and the negative electrode active material can be selected from any one or a combination of graphite-type carbon, oxide materials or lithium; in, The negative electrode using the negative electrode active material contains carbon as a conductive material and a binder, and the negative electrode active material is graphite-type carbon and / or an oxide material.
3. A lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 1 or 2, wherein the most preferred negative electrode active material is graphite-type carbon.
4. A lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 2 or 3, wherein the most preferred negative electrode active material of graphite-type carbon is artificial graphite.
5. A lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to any one of claims 1 to 4, wherein the carbon used as the conductive material can be selected from any one of carbon black, nanocarbon or graphite, or a combination thereof.
6. A lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to any one of claims 1, 2 or 5, wherein the most preferred carbon used as the conductive material is carbon black.
7. A lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 1 or 2, wherein the binder for the positive electrode and the negative electrode can be selected from any one of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose, butadiene rubber, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA) or polyacrylic acid or a combination thereof.
8. A lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as a shell according to claim 1 or 7, wherein the most preferred binder used with the positive electrode is polyvinylidene fluoride (PVDF).
9. A lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 1, wherein the weight ratio of the NMC material (LiNMC or NMC) as a core and the carbon black as an outer shell of the positive electrode active material is preferably in the range of 98:2-99:
1.
10. A lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 1 or 9, wherein the weight ratio of the NMC material (LiNMC or NMC) as a core to the carbon black as an outer shell of the positive electrode active material is most preferably 99:
1.
11. A lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to any one of claims 1 or 5 to 10, wherein the positive electrode has an NMC material core and a carbon black outer shell (NMC@C): carbon used as a conductive material: a binder in a weight ratio of 80-99:0.5-10:0.5-10 respectively.
12. A lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to any one of claims 1 or 5 to 11, wherein the positive electrode has an NMC material core and a carbon black outer shell (NMC@C): carbon used as a conductive material: a binder in an optimal weight ratio of 94:4:2 respectively.
13. A lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to any one of claims 1 to 7, wherein the binder used with the negative electrode is most preferably carboxymethyl cellulose (CMC) and / or styrene-butadiene rubber (SBR).
14. A lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to any one of claims 1 to 7 or 13, wherein the negative electrode has a negative electrode active material component: carbon as a conductive material: carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) in a weight ratio of 80-98.5:0.5-10:0.5-5:0.5-5, and the negative electrode active material component is graphite carbon or oxide material.
15. A lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to any one of claims 1 to 7 or 13 to 14, wherein the negative electrode has a negative electrode active material component: carbon as a conductive material: carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) in a weight ratio of preferably 94.5:1:2.25:2.25 respectively, and the negative electrode active material component is graphite carbon or oxide material.
16. The lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 1, wherein the electrolyte solution comprises a lithium salt, a solvent and an additive, wherein: A. The lithium salt is lithium hexafluorophosphate (LiPF6) with a concentration range of 1.0-1.5 molar; B. the solvent may be selected from any one or a combination of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC); C. The additive can be selected from any one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), propane sultone (PS), lithium difluorophosphate (LiPO2F2), methylene methanedisulfonate (MMDS) or a combination thereof, and its usage is 0.1-12% of the weight of the electrolyte solution.
17. A lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 16, wherein the solvent has a weight ratio of ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) of 5-30:5-40:30-90 respectively.
18. A lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as a shell according to any one of claims 16 to 17, wherein the solvent preferably has a weight ratio of ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) of 25:5:70 respectively.
19. The lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 16, wherein preferred additives include: Vinylene carbonate (VC), the amount of which is 2% by weight of the electrolyte solution, and any one or a combination of fluoroethylene carbonate (FEC), propane sultone (PS), lithium difluorophosphate (LiPO2F2), and methylene methanedisulfonate (MMDS) additives, the amount of which is 0.1-10% by weight of the electrolyte solution.
20. A lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 16 or 19, wherein the most preferred additives include vinylene carbonate (VC) and fluoroethylene carbonate (FEC), and the amounts thereof are 2% and 0.1% by weight of the electrolyte solution, respectively.
21. A lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 1 or 16, wherein the most preferred electrolyte solution comprises lithium hexafluorophosphate at a concentration of 1.2 moles, wherein the weight proportion of ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) solvents is 25:5:70 respectively, and the electrolyte solution also comprises additives of vinylene carbonate (VC) and fluoroethylene carbonate (FEC), and the amounts thereof are 2% and 0.1% by weight of the electrolyte solution respectively.
22. A method for preparing a lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell, comprising: A. preparing the positive electrode, using mechanical melting to mix the NMC material as the core and the carbon black as the shell to make a positive electrode active material; The positive electrode active material is mixed with carbon used as a conductive material and a binder; the prepared positive electrode is then coated on an aluminum foil; and dried; B. Preparation of negative electrode; C. preparing an electrolyte solution comprising a lithium hexafluorophosphate (LiPF6) salt, a solvent and an additive; D. assembling the lithium ion battery using the positive electrode prepared in step A, the negative electrode prepared in step B, a polymer film as an electrode separator, and the electrolyte solution as an ion conductor prepared in step C; According to the negative electrode active material, step B of preparing the negative electrode can be implemented by two processes, wherein: The first process, wherein the negative electrode uses a negative electrode active material, the negative electrode active material is graphite-type carbon and / or oxide material, which has the following steps: using a high-energy ball mill to grind the graphite-type carbon or oxide material; then adding carbon used as a conductive material, a binder and an organic solvent, wherein the organic solvent can be selected from any one of N-methyl-2-pyrrolidone, ethanol or water or a combination thereof; then coating the prepared negative electrode on a copper foil; and then drying; as well as The second process uses a negative electrode having a negative electrode active material, which is lithium metal in the form of lithium metal sheets.
23. The method for preparing a lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 22, wherein the preferred negative electrode active material is graphite-type carbon.
24. A method for preparing a lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 22 or 23, wherein the most preferred negative electrode active material of graphite-type carbon is artificial graphite.
25. The method for preparing a lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 22, wherein the positive electrode contains a positive electrode active material in the form of a metal oxide core and an outer shell (core@shell); that is, an NMC material (LiNMC or NMC) as a metal oxide core and carbon black as an outer shell (NMC@C), wherein the weight ratio of the NMC material (LiNMC or NMC) as the core to the carbon black as the outer shell is in the range of 95.01:4.99-99.5:0.5, and the positive electrode also includes carbon used as a conductive material and a binder.
26. The method for preparing a lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 22 or 25, wherein the carbon used as the conductive material can be selected from any one of carbon black, nanocarbon and graphite or a combination thereof.
27. A method for preparing a lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as a shell according to any one of claims 22 or 25 to 26, wherein the best carbon used as a conductive material is carbon black.
28. A method for preparing a lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as a shell according to claim 22 or 25, wherein the binder for the positive electrode and the negative electrode can be selected from any one of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose, butadiene rubber, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA) or polyacrylic acid or a combination thereof.
29. A method for preparing a lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as a shell according to any one of claims 22, 25 or 28, wherein the most preferred binder used with the positive electrode is polyvinylidene fluoride (PVDF).
30. A method for preparing a lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 22 or 25, wherein the weight ratio of the NMC material (LiNMC or NMC) as a core and the carbon black as an outer shell of the positive electrode active material is preferably in the range of 98:2-99:
1.
31. A method for preparing a lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 22, 25 or 30, wherein the positive electrode active material has an NMC material (LiNMC or NMC) as a core and carbon black as an outer shell in a most preferred weight ratio of 99:
1.
32. A method for preparing a lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to any one of claims 22 or 25 or 30 to 31, wherein the positive electrode has an NMC material core and a carbon black outer shell (NMC@C): carbon used as a conductive material: a binder in a weight ratio of 80-99:0.5-10:0.5-10 respectively.
33. A method for preparing a lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to any one of claims 22 or 25 or 30 to 32, wherein the positive electrode has an NMC material core and a carbon black outer shell (NMC@C): carbon as a conductive material: an optimal composition ratio of the binder is 94:4:2 by weight.
34. A method for preparing a lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as a shell according to any one of claims 22 or 25 or 28 to 29 or 32 to 33, wherein the most preferred binder for use with the negative electrode is carboxymethyl cellulose (CMC) and / or styrene-butadiene rubber (SBR).
35. A method for preparing a lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to any one of claims 22 to 24 or 34, wherein the negative electrode has a negative electrode active material component: carbon as a conductive material: carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) in a weight ratio of 80-98.5:0.5-10:0.5-5:0.5-5, and the negative electrode active material component is graphite carbon or oxide material.
36. A method for preparing a lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to any one of claims 22 to 24 or 35, wherein the negative electrode has an optimal composition ratio of negative electrode active material: carbon as a conductive material: carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) in weight parts of 94.5:1:2.25:2.25 respectively.
37. The method for preparing a lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 22, wherein the electrolyte solution comprises a lithium salt, a solvent and an additive, wherein: A. The lithium salt is lithium hexafluorophosphate (LiPF6) with a concentration range of 1.0-1.5 molar; B. the solvent may be selected from any one or a combination of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC); C. The additive can be selected from any one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), propane sultone (PS), lithium difluorophosphate (LiPO2F2), methylene methanedisulfonate (MMDS) or a combination thereof, and its usage is 0.1-12% of the weight of the electrolyte solution.
38. A method for preparing a lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 22 or 37, wherein the solvent has a ratio of ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) of 5-30:5-40:30-90 in parts by weight of the electrolyte solution.
39. A method for preparing a lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to any one of claims 22 or 37 to 38, wherein the solvent has an optimal ratio of ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) of 25:5:70 in terms of the weight of the electrolyte solution.
40. A method for preparing a lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 22 or 37, wherein the preferred additives include: Vinylene carbonate (VC), the amount of which is 2% by weight of the electrolyte solution; And any one or a combination of fluoroethylene carbonate (FEC), propane sultone (PS), lithium difluorophosphate (LiPO2F2), methylene disulfonate (MMDS) additives, and the amount thereof is 0.1-10% by weight of the electrolyte solution.
41. A method for preparing a lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as a shell according to any one of claims 22, 37 or 40, wherein the most preferred additives include vinylene carbonate (VC) and fluoroethylene carbonate (FEC), and the amounts thereof are 2% and 0.1% by weight of the electrolyte solution, respectively.
42. A method for preparing a lithium ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 22 or 37, wherein the most preferred electrolyte solution comprises: Lithium hexafluorophosphate with a concentration of 1.2 molar, wherein the weight ratio of ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) solvent is 25:5:70; and vinylene carbonate (VC) and fluoroethylene carbonate (FEC) additives, the amounts of which are 2% and 0.1% of the weight of the electrolyte solution respectively.
43. A method for preparing a lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as an outer shell according to claim 22, wherein the positive electrode prepared and coated on an aluminum foil has a positive electrode weight in the range of 17-23 mg per square centimeter and a thickness in the range of 110-250 microns.
44. A method for preparing a lithium-ion battery having a positive electrode comprising an NMC material as a core and carbon black as a shell according to claim 22, wherein the negative electrode comprising a negative electrode active material prepared and coated on a copper foil has a negative electrode weight in the range of 10-15 mg per square centimeter, a thickness in the range of 100-250 microns, and the negative electrode active material is a graphite-type carbon or oxide material.
Citation Information
Patent Citations
Core-shell structure NCM (nickel manganese cobalt) ternary cathode material containing carbon nanotube and preparation method thereof
CN108539193A
Core-shell structure positive electrode material and preparation method thereof and application thereof
CN111354936A
Preparation method of graphene-coated nickel-cobalt-manganese ternary positive electrode material
CN112331830A
Lithium ion secondary battery
US10897062B2
Negative electrode active material and method of preparing the same
US11152621B2